A model of an office information system for an academic institute - Canlas, Marian Libunao; Kanchit Malaivongs; Aagesen, Finn Arve; Gonzales, Jr. R. L.; Government of Japan (Bangkok : Asian Institute of Technology, 1986)
This study on the Office Information System of the Asian Institute of Technology is divided in to three major parts , namely , the analysis of requirements , the development of a proposed system, and the analysis of PROFS as a possible tool in the implementation of the proposed system. The analysis of requirements involves a survey on how the present system operates and an evaluation on what improvements are needed by the system. Several steps are undertaken in the development of the proposed OIS . The concept of an ideal office is considered first with the introduction of a way on how to represent the ideal office architecture. A representation of the present system is then constructed to show its differences with the ideal. Base don the requirements , the ideal office system, and the present system, the proposed system is created. There are two parts in the creation of the proposed system, first is the conceptual modeling of the proposed office system architecture where the network configuration is presented, and second is the modeling of the office procedures using the structured specification technique. The conceptual system architecture and the specifications of the office procedures complete the model of the Office Information System for AIT . The analysis of PROFS is don e by comparing its capabilities with that of the proposed system, taking into account the strength sand weaknesses of PROFS . Recommendations on the implementation of the system , with the approximate costs to be incurred, are presented after reasonable conclusion have been derived.
A thesis submitted in partial fulfillment of the requirements for t he degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Information storage and retrieval systems